Beyond Jewish Identity Rethinking Concepts and Imagining Alternatives - Kelman, Ari Y.; Levisohn, Jon A. (Academic Studies Press, 2020)
This volume, the first collection to examine critically the relationship between Jewish education and Jewish identity, makes two important interventions. First, it offers a critical assessment of the relationship between education and identity, arguing that the reification of identity has hampered much educational creativity in the pursuit of this goal, and that the nearly ubiquitous employment of the term obscures significant questions about what Jewish education is and ought to be. Second, this volume offers thoughtful responses that are not merely synonymous replacements for "identity," suggesting new possibilities for how to think about the purposes and desired outcomes of Jewish education, potentially contributing to any number of new conversations about the relationship between Jewish education and Jewish life.